PERAN SIKAP DALAM MEMEDIASI PENGARUH KEPEDULIAN LINGKUNGAN TERHADAP NIAT BELI PRODUK RAMAH LINGKUNGAN (STUDI PADA PRODUK TUPPERWARE) - Saraswaty, Wulan; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen; Vol 4 No 8 (2015), 2015)
This study aims to: (1) Determine the influence of environmental concerns on attitudes to the environment; (2) Determine the influence of environmental concerns on consumer purchase intention Tupperware environmentally friendly products; (3) Determine the influence of attitudes toward consumer purchase intentions Tupperware environmentally friendly products; (4) Determine the role of attitude in mediating the environmental awareness of the intention to buy environmentally friendly products Tupperware. The study was conducted in the city of Denpasar and Badung. The data is taken from a sample of 110 people by using a questionnaire as a data collection instrument. Furthermore, the data were analyzed using path analysis (path analysis) .The result showed that: (1) Concern environment and a significant positive effect on attitudes towards the environment; (2) Concern environment positive and significant effect on the intention to buy environmentally friendly products Tupperware in Denpasar city and Badung Regency (3) attitude towards the environment positive and significant effect on the intention to buy environmentally friendly products Tupperware in Denpasar city and Badung Regency ; (4) The attitude mediates the influence of environmental concerns on the intention to buy environmentally friendly products Tupperware in Denpasar city and Badung Regency .
Keywords: environmental awareness, attitude, intention to buy environmentally friendly products